Asphalt mixture selection - Nicholls, Cliff; Hannah, Arthur (Boca Raton : CRC, Taylor & Francis, 2019)
"This practical guide starts with a survey of the types of site and the asphalt properties which are required. Various external influences which may affect the relative importance of some properties are addressed, and the interplay of sites and external is considered. Asphalt mixture types and their properties are reviewed, largely as defined in the EN 13108 series but subdivided into further categories, and into maximum nominal coarse aggregate sizes using EN 13043 basic set plus set 2 sizes. Guidance is given, including using flowcharts, of the different mixtures that are suitable for each situation. In some cases a range of choices or mixtures with different degrees of suitability is offered. The guidance covers surface course, binder course and base, but with more focus on the surface course where the external influence is most significant. The site and external influence combinations on which a mixture can be used successfully are also given. The book is primarily intended for those who select asphalt on an occasional basis, such as architects or housing developers, but could be of use to other engineers with limited experience. It is also useful as an educational textbook for those studying asphalt technology"--
OCLC-licensed vendor bibliographic record.
Keywords: Asphalt emulsion mixtures; TECHNOLOGY / Construction / General